Management of islamic educational institutions madrasah - Amir Syarifuddin Mukhtar; Maemunah Sa’diyah; Fouad Larhzizar (At Turots: Jurnal Pendidikan Islam, 2024)
This research aims to ensure that Islamic educational institutions, especially madrasas, can compete and continue to exist in society, and the importance of managing the management of madrasah educational institutions with an approach to the concept of Islamic management. This study uses a Literature Study approach to collect information and data. The data of this research comes from primary data (books, literature, journals) and secondary data (observations on madrasah educational institutions). The data collection technique is carried out with a literature approach. The data collected is then analyzed and adjusted to the current institutional conditions of madrasah education. And the result of this research is that Islamic educational institutions require high professionalism, but also a sacred mission and a strong mentality with an approach that combines managerial skills and leadership spirit in accordance with Islamic principles as a caliphate. And back to the concept that madrassas are the first model of education given by Allah to Adam (as), as stated in QS Al-Baqarah [2]:31, where Allah taught Adam the names of things. Overall, management functions can achieve effective and efficient goals through a careful planning process, good organization, targeted implementation, and strict supervision.